Spatial Planning in Perspective of Good Governance (A Study on Analysis of Spatial Planning in Batu City as a Tourism City) - Retno Wulan Sekarsari; Andy Fefta Wijaya (Program Pascasarjana, 2014)
Spatial planning is an effort to improve the welfare of the community and to ensure environmental sustainability by taking into account the comparative advantages in an area and minimizing the development gap by reducing slums, and poor and underdeveloped areas. Regional Spatial Planning Policy is a kind ofÂ policy product to control the level of environmental damage and the disorganized development and growth in a city or regency. The role of Batu City Government is to realize Batu City space that is safe, comfortable, productive and sustainable as a superior agropolitan city and tourism city in East Java Province. This article utilized Good Governance Perspective and System Theory to analyze the formulation of Regional Spatial Planning Policy in Batu City. This article firstly explained about tourism development, and secondly described the authority and responsibility of stakeholders in spatial planning formulation. The third part clarified good governance perspective on spatial planning in Batu City and analyzed supporting and inhibiting factors in spatial planning formulation in Batu City. The findings showed that only some actors and factors had strong influence over the formulation of Regional Spatial Planning Policy. Keywords: Good Governace, Governace Perspective, Spatial Planning, Tourism City, Batu City